Subcutaneous Anti-D versus intravenous methylprednisolone for the treatment of immune thrombocytopenic purpura - Sharmeen, Olia; Rashid, Mohammod Hasanur; Rouf, Md Abdur; Islam, Afiqul (International Journal of Contemporary Pediatrics, 2018)
Background: Established treatment option for immune thrombocytopenic purpura (ITP) are intravenous immunoglobulin (IVIg), anti-D immunoglobulin’ and high dose intravenous methyl prednisolone (HIVMP). The present study was undertaken to compare the efficacy of subcutaneous bolus anti-D over HIVMP in the treatment of ITP. Methods: A randomized clinical trial was conducted on a total 20 children with ITP, presented with extensive bleeding manifestation and platelet count <20 × 109/L;10 children received single dose subcutaneous anti-D (75 microgram/kg) and 10 children received HIVMP (30 mg/kg/dose) for 3 consecutive days. Patients were monitored for response to treatment and adverse events, platelet count and hemoglobin label were done in all patients at 24-hour, 48-hour, 72 hour, 1st week, 2nd week, 1st month, 2nd month and 3rd month after treatment to observe the change. Response rate define as a platelet count over 20 × 109/L within 72 hours of treatment. All the data were analyzed with the help of SPSS software version 16.0. Results: By 24 hours of treatment 40% patient of anti-D and 10% patients of HIVMP group had platelet count >20 x109/L, by 72 hours 90% patients of both group achieved complete response (P =1.750). In HIVMP group the rate of remission gradually decreasing but in anti-D group it was persistently remain high. In anti-D group hemoglobin concentration decreased in 80% cases (P=0.023) but rate of decrease was not significant. New hemorrhage or significant extension of hemorrhage did not observe in any group. Conclusions: A single dose of subcutaneous anti-D raised platelet count in children with ITP more rapidly and effectively than HIVMP (30 mg/kg/dose) with an acceptable safety profile.